The Effect of Nim, Npl, Firm Size and Exchange Rate on Profitability with Car as an Intervening Variable in the Company Conventional Banking Sector Registered In Indonesia Stock Exchange 2015-2019 Period - Dwilita, Handriyani; Mingka, Alfan Yuharbi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
Purpose: The purpose of this study was to determine the effect of NIM, NPL, Firm Size and Exchange Rate on ROA with CAR as the intervening variable. The problem in this research is the finding of inconsistencies between theory and the phenomena behind the change in ROA. Methods: The data analysis method used in this study is multiple linear regression analysis, classical assumption test, and Sobel test to determine the effect of mediation (intervening). Findings: Based on the results of the study, it is known that NIM has no effect on CAR with a significance value of 0.092 ≥ 0.05 and NIM has an effect on ROA with a significance value of 0.000 ≤ 0.05. NPL has an effect on CAR with a significance value of 0.006 ≤ 0.05 and NPL has an effect on ROA with a significance value of 0.000 ≤ 0.05. Firm Size has an effect on CAR with a significance value of 0.021 ≤ 0.05, and Firm Size has an effect on ROA with a significance value of 0.002 ≤ 0.05 and Exchange Rate has no effect on CAR with a significance value of 0.757 ≥ 0.05 and Exchange Rate has no effect on ROA with a significance value of 0.949 ≥ 0.05. Meanwhile, for the two regressions, NIM, NPL, Firm Size and Exchange Rate have a simultaneous effect on CAR and ROA with a significance value of 0.001 and 0.000. Based on the results of the Sobel test and t arithmetic, it was found that the CAR variable was not able to mediate the effect of NIM, NPL, Firm Size and Exchange Rate on ROA. Originality: This study adds an intervening variable (mediation) in order to determine whether CAR is able to mediate the effect of NIM, NPL, Firm Size and Exchange Rate on ROA.